siRNA for REST ameliorates symptoms in ALS mice and serum REST predicts disease prognosis and survival in ALS patients - Guida, Natascia; Valsecchi, Valeria; Anzilotti, Serenella; Dubbioso, Raffaele; Cuomo, Ornella; Ruggiero, Silvia; Senerchia, Gianmaria; Iuzzolino, Valentina Virginia; Kolici, Xhesika; De Iesu, Nunzia; Pignataro, Giuseppe; Annunziato, Lucio; et al. (Molecular therapy, 2025)
Restrictive element-1 silencing transcription factor (REST) is a key repressor of neuronal genes in stem cells and neuronal progenitor cells and its aberrant accumulation has been implicated in the pathophysiology of neurological disorders, such as Huntington's disease, epilepsy, and stroke. Herein, we investigated the role of REST in amyotrophic lateral sclerosis (ALS) pathophysiology and its potential as blood-based predictor of disease prognosis and survival in ALS patients. Intriguingly, REST protein levels were significantly increased in motor cortex, brainstem and spinal cord of superoxide dismutase 1 (SOD1)-G93A mice compared with wild-type mice, both during early and late symptomatic phases of the disease. Notably, intracerebroventricular injections of a siRNA against REST (siREST), mitigated motor neuron loss, counteracted the formation of SOD1 aggregates, and reduced astrogliosis, thus improving behavioral performance and extending the survival of SOD1-G93A mice. Interestingly, ELISA assay showed that serum REST levels were significantly elevated in ALS patients compared with healthy subjects; furthermore, the higher serum REST levels have been found in patients with shorter tracheostomy-free survival. Collectively, we demonstrated that preventing REST increase in brain areas involved in ALS disorder extended the survival of SOD1-G93A mice and showed that serum REST may represent a possible prognostic biomarker in ALS patients.